Reading and dyslexia : visual and attentional processes - Everatt, John (London ; New York : Routledge, 1999)
Associations between reading ability and visual processes. The effects of different types of text presentation on children with a specific reading disability. How dyslexics see and learn to read well. Saccadic eye movements in dyslexia. Motor aspects of dyslexia. Anatomy, circuitry and plasticity of word reading. Filtering performance by good and poor readers. Attention and eye movements in reading.
Keywords: Education; Reading; Dyslexia; Dyslexia; Visual perception; Reading -- Physiological aspects; Reading disability -- Physiological aspects; Visual learning